Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1089/tmj.2008.0112
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Use of Personal Digital Assistants Among Physicians

Abstract: The objective of this study was to examine the factors that might influence the use of personal digital assistant devices (PDAs) by physicians for assistance in the delivery of their routine patient care. An Internet-based single-institution survey was done of internal medicine resident physicians. None of the baseline demographic characteristics measured were associated with whether PDAs were being used or not by resident physicians in patient care. Resident physicians who used their PDAs for medical purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Those not classified as a primary care physician indicated that they were in specialty ambulatory care practices. The distribution of respondents by these demographic characteristics was comparable to the national data generated from the AMA workforce statistics on physicians in the United States [14].…”
Section: Physician and Practice Characteristicssupporting
confidence: 59%
See 1 more Smart Citation
“…Those not classified as a primary care physician indicated that they were in specialty ambulatory care practices. The distribution of respondents by these demographic characteristics was comparable to the national data generated from the AMA workforce statistics on physicians in the United States [14].…”
Section: Physician and Practice Characteristicssupporting
confidence: 59%
“…A longitudinal study of PDA use by medical students, residents and staff determined that their reasons for use are to access drug references, medical references and medical calculators; a high rate of acceptance and longitudinal use was observed [13]. Studies about PDA users indicate that they believe PDA use supports clinical decision making, promotes patient safety, and improves productivity and efficiency [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further, some studies also showed significant correlations among the identified factors. Perceived usefulness had the strongest impact on health care providers’ behavior intention [88], whereas their perceived usefulness was influenced by the perceived ease of use, eHealth and business process alignment, end user involvement, management commitment and support to change, health care provider-patient relationship, and IT experience and knowledge [25,28,33,56,77,83,86-88]. The variance of the perceived ease of use was associated with the computer self-efficacy, end user involvement, management commitment and support to change, as well as health care provider-patient relationship [77,88].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of physicians in other clinical environments have found mobile device adoption rates of up to 86% 21,22 with access to drug references consistently among the leading uses. 21,23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies of clinical uses of mobile devices have seen a form of technology-affinity effect, with positive attitudes toward the technology, changes in practice, and changes in outcomes associated primarily with clinicians who were more active users of technology. 36,37 Utilization rates may be lower for less enthusiastic practitioners. Finally, the results of this study may differ over time, as mobile device use amongst physicians has increased and the operating systems running on these devices has changed considerably since the survey was administered.…”
Section: Discussionmentioning
confidence: 99%